Fish assemblage in the Pearl River Estuary: Spatial‐seasonal variation, environmental influence and trends over the past three decades - Zhou, Lei; Wang, Gongpei; Kuang, Tianxu; Guo, Dingli; Li, Guifeng (Journal of applied ichthyology, 2019)
The Pearl River Estuary is the largest estuary in South China and plays a considerable role in the local fisheries economy, yet little is known about the current state of fish assemblage in this ecosystem. To quantify spatial‐seasonal variations, environmental influences, and trends over the past three decades of the fish assemblage in the Pearl River Estuary, we sampled 11 sites seasonally from December 2013 to September 2016. Throughout the study, 285 species from 88 families and 195 genera were collected. There were obvious spatial and seasonal variations of the fish assemblage in terms of the dominant species, species richness, and composition of ecological types. Mouth distance, NH4+ N, chlorophyll‐a, flow, DO, salinity and water transparency were the main variables influencing the spatial‐temporal dynamic of fishes within the estuarine systems. Compared with the record of 330 species in the 1980s, the number of fish species in the Pearl River Estuary has declined by 45 fish species. The Jaccard's similarity of fish composition between the historical investigation (the 1980's) and the present investigation (2013–2016) was 0.62, with 95 species undiscovered and 50 species increased in the present study compared to the 1980s, indicating the assemblage structure has obviously changed. However, in term of ecological guilds, there was no significant difference in the composition of all the selected ecological traits between these two periods. Anthropogenic activities including overfishing, introducing alien fish, dam construction and pollution were considered the main disturbance on fish composition over the past three decades. We conclude that there existed pronounced spatiotemporal changes of fish assemblages, which arises from the compounding effects of environmental factors and anthropogenic activities. These findings are beneficial to understanding and developing suitable conservation strategies for the management and protection of fish resources in the Pearl River Estuary.